A Flow Cytometry-Based Whole Blood Natural Killer Cell Cytotoxicity Assay Using Overnight Cytokine Activation - Kim, Jinho; Phan, Minh-Trang Thi; Kweon, SoonHo; Yu, HongBi; Park, Jeehun; Kim, Kyeong-Hee; Hwang, Ilwoong; Han, Sangbin; Kwon, Min-Jung; Cho, Duck (Frontiers in Immunology, 2020)
ABSTRACT Background: Measurement of natural killer (NK) cell function has important clinical utility in several diseases. Although the flow cytometry (FC)-based 4-h NK cytotoxicity assay using peripheral blood mononuclear cells (PBMCs) in the clinical laboratory has been used for this purpose, this assay requires large amounts of blood and a rapid PBMC isolation step. Here, we developed an FC-based overnight NK cytotoxicity assay using whole blood (WB), and applied it to patients with liver diseases. Methods: Peripheral blood of healthy volunteers (n = 28) and patients with liver diseases, including hepatocellular carcinoma (n = 19) and liver cirrhosis (n = 7), was analyzed for complete blood count, absolute NK cell count, and NK cell activity (NKA). NKA was evaluated in three assay types: an FC-based overnight WB NK cytotoxicity assay using carboxyfluorescein diacetate succinimidyl ester-labeled K562 cells in the presence of various cytokine combinations (including interleukin (IL)-2, IL-18, and IL-21), an FC-based 4-h PBMC NK cytotoxicity assay, and an FC-based CD107a degranulation assay using WB and PBMCs. Results: Optimal cytokine combinations for NK cell activation in WB were determined (IL-2/IL-18, IL-2/IL-21, and IL-2/IL-18/IL-21). A good correlation was observed between WB and PBMC NK cytotoxicity assays; absolute NK cell counts were better correlated with the WB NK cytotoxicity assay than with the PBMC NK cytotoxicity assay. This WB NK cytotoxicity assay showed that patients with liver diseases had significantly lower NK cytotoxicity than healthy volunteers, under stimulation with various cytokines (p < 0.001). Conclusion: The proposed FC-based overnight WB NK cytotoxicity assay correlates well with the conventional 4-h PBMC NK cytotoxicity assay, demonstrating future potential as a supportive assay for clinical laboratory research and observational studies.